2022
DOI: 10.2147/prbm.s371945
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Taoism on Employee Low-Carbon Behavior in China: The Mediating Role of Perceived Value and Guanxi

Abstract: Purpose We established a dual-pathway model in which Taoism at work can shape employee low-carbon behavior via two mediating mechanisms: perceived value as a psychological mediator and guanxi as a social mediator. Patients and Methods Data were collected from 788 Chinese enterprises employees. Results Our results confirm the direct positive effect of Taoism on employee low-carbon behavior and the partial mediating effects of perceived value a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Prior to analysis, we processed the data using item parcelling, a technique widely utilized in social science research (e.g., Zhang et al [95]). Initially, we calculated the mean of all items and used this as the unit of analysis.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…Prior to analysis, we processed the data using item parcelling, a technique widely utilized in social science research (e.g., Zhang et al [95]). Initially, we calculated the mean of all items and used this as the unit of analysis.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…The similarities and differences in perceived value could lead to different behaviors. Followers who have the same moral type as leaders in the organization perceive higher value and lower risk, and leads positive results at work ( Zhang et al, 2022 ). In contrast, followers who have different ethical types than leaders feel less value, more risk, and are unable to identify with the organization’s behavior, which go against to team development.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…Future research can consider the impact of green HRM on green technology innovation [ 66 ]. Previous research has found that guanxi [ 67 , 68 ] and psychological contracts [ 68 ] influence employee green behaviour. Follow-up research can also start from these aspects and conduct cross-level research to explore its impact on individual behaviour to promote the development of this field.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%